2019
DOI: 10.1002/fsn3.884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of domestic cooking on rice protein digestibility

Abstract: The effects of washing, soaking, and common domestic cooking methods (normal cooking, high‐pressure cooking, and microwave cooking) on protein content, in vitro protein digestibility, and amino acid composition of japonica and indica rice were investigated. All processes in rice domestic cooking did not affect protein content. However, the gastric and gastrointestinal protein digestibilities decreased significantly after cooking. Protein solubility methods were used to observe the formation of disulfide bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 24 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Surprisingly, REP's protein efficiency ratio using alkali treatment was equivalent to that of casein. This was recently confirmed by Liu et al (17), who found that cooking induced disulfide bond cross-linking and decreased prolamin digestibility. After heat treatment like cooking, prolamin may still be indigestible; therefore, it can be regarded as a kind of resistant protein.…”
Section: Rice Endosperm Proteinsupporting
confidence: 61%
“…Surprisingly, REP's protein efficiency ratio using alkali treatment was equivalent to that of casein. This was recently confirmed by Liu et al (17), who found that cooking induced disulfide bond cross-linking and decreased prolamin digestibility. After heat treatment like cooking, prolamin may still be indigestible; therefore, it can be regarded as a kind of resistant protein.…”
Section: Rice Endosperm Proteinsupporting
confidence: 61%
“…Processing and especially cooking can considerably affect amino acid composition and digestibility of proteins, resulting in a different DIAAS (Bailey, Mathai, Berg, & Stein, 2019; Friedman, Gumbmann, & Masters, 1984). While heat treatment can inactivate some of the ANFs, it can also induce molecular alterations making the protein more resistant to the action of digestive proteases or on the contrary more accessible (Carbonaro, Cappelloni, Nicoli, Lucarini, & Carnovale, 1997; Duodu, Taylor, Belton, & Hamaker, 2003; Liu, Zheng, & Chen, 2019). This is also illustrated in the present study in which pea protein obtains an average DIAAS of 70 while after extrusion its DIAAS can increase to 82 or 86 depending upon the extrusion temperature (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Studies describing both a reduction and increase of the protein digestibility can, hence, be found. While high pressure cooking of rice e.g., reduced the protein digestibility more than regular cooking [60], high pressure cooking has also been reported to improve the in vitro protein digestibility of cowpeas [61]. Moreover, high pressure treatments have been proven to avoid or revert the digestibility decreasing effect of cooking on sorghum proteins [62].…”
Section: Protein Digestibilitymentioning
confidence: 99%